Prevalence of palate-gingival groove in patients of Dhulikhel Hospital - Shreshta, D; Humagain, M; Swastika, S (Journal of College of Medical Sciences-Nepal, 2015)
Background: Palato-gingival groove is a rare developmental anomaly leading to pulpal and periodontal diseases. Radicular extensions of these grooves are areas for plaque accumulation which are difficult to clean. Its clinical and radiographic findings mimic endo-perio lesions leading to diagnostic dilemma, ineffective treatment attempts and treatment failures. Objectives: To investigate the prevalence of coronal and radicular palato-gingival groove in dental patients visiting Dhulikhel Hospital and its association with gingival disease. Methods: Patients (N=231) visiting dental out-patient department of Dhulikhel Hospital, were examined for the presence or absence of palato-gingival groove in maxillary anteriors. Loe and Silness Gingival index was also recorded for all the patients using University of North Caroline-15 periodontal probe. Chisquare test was used to test the association of the presence of palato-gingival groove and gingival disease. P value of <0.05 was considered to be significant. Results: A total of 1362 maxillary anterior teeth were included in the study. The prevalence of coronal palatogingival groove among 1362 teeth was 6.6%. Coronal palato-gingival grooves were more common in females (56.6%) than in male (43.3%) patients. Prevalence of radicular groove was only 0.88% for lateral incisors and 0.2% for canines. There was no significant association between palate-gingival groove and gingival disease (P=0.91). Conclusion: The prevalence of palato-gingival groove is common in dental patients visiting Dhulikhel Hospital. Gingival disease is not significantly associated with palate-gingival groove. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12765 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 32-36